A Comparative Analysis of the Social and Demographic Factors in Ghanaian Political Party Affiliations - Kpessa-Whyte, M.; Abu, M. (Taylor & Francis Group, 2021)
Since 1992, political power in Ghana alternates between the National Democratic Congress (NDC) and the New Patriotic Party (NPP). Yet beyond extrapolations from previous election results not much is known about the socio-demographic characteristics of the core membership of these two political parties. Using data from the Ghana Opinion Poll study conducted by the Centre for Policy Research and the Fredrich Ebert Stiftung, Ghana in April 2018, this study employed a multinomial logistic regression model to understand the social and demographic features around which support for the political parties in Ghana coalesced. We found that age of the respondent, education, employment, region of residence, ethnicity and religion are significant predictors of partisan affiliation. Notwithstanding the NDC’s electoral success over the years, we observe a process of political realignment that favours the NPP across most of the demographic variables analysed. The study has implications for the mobilisation and recruitment strategies of both political parties.
Research Article